Effect of Thermal Treatment on the Morphology of ZnS: Mn Nanocrystal - Mohammad Syuhaimi, Ab-Rahman; Noor Azie Azura, Mohd Arif; Sahbudin, Shaari (IDOSI Publication, 2011)
The arrangement, structure and formation of nanocrystals depend on the thermal treatment. This work focuses on the influences of the thermal treatment of manganese-doped zinc sulphide (ZnS:Mn) nanocrystals on their self-arrangement. A film was prepared by the sol gel method and layered by spin coating after 48 hours of stirring. We have found that a nanocrystalline layer of good quality can be obtained if a longer annealing treatment is applied.